The Relationship between the role of parent and self-Esteem to acceptance parents with mentally retarded children in Extraordinary school Bf Mandara Kendari Indonesia - Wahyuni, Sri (Sahabat Publikasi Kuu, 2024)
Children and adolescents with intellectual disabilities have a higher prevalence (18.30/1000) than adults (4.94/1000). Furthermore, it is estimated that around 1% of children between the ages of 3 and 10 are affected by intellectual disability worldwide. The purpose of this study was to determine the relationship between the role of parents and self-esteem towards the acceptance of parents with mentally retarded children at the extraordinary school Mandara Kendari, Indonesia.The research method uses quantitative research with a cross sectional design. The population of all parents of children with mental retardation is 340. The research sample consists of 184 respondents. Data analysis using chi-square analysis. Based on the chi-square test, there were 79 respondents (42.9%) in the category of good parental roles and 105 respondents in the poor parental role category, while in the class of parents with good self-esteem, there were 67 respondents (36.5%) and in the type of low self-esteem, there were 117 respondents. With a 95% confidence interval of 0.05, the result is a p-value of 0.05. The conclusion is that the role of parents and self-esteem have a relationship with the acceptance of parents with mentally retarded children at BF Mandara Kendari Extraordinary School, Indonesia.